Perlindungan Hukum Atas Lagu Yang Di Cover Tanpa Izin Pemegang Hak Cipta - Jaka, Jaka; Narwadan, Theresia Nolda Agnes; Balik, Agustina (Faculty of Law Universitas Pattimura, 2025)
Copyright is regulated by the Copyright Law No. 28 of 2014. The definition of copyright in this law is the exclusive right for creators or recipients of rights to announce or reproduce their work or grant permission for it, without reducing the limitations under the applicable legislation as stated in Article 12, paragraph (1) and paragraph (2). The Warkopi group is one of the groups that resemble the members of Warkop DKI, namely Dono, Kasino, and Indro. The Warkopi group committed a copyright infringement by intentionally plagiarizing and mimicking the works of Warkop DKI in the form of a photoshoot session for a short film in which the Warkopi members performed. This action violates copyright law, specifically Articles 12, paragraph (1) and (2). This research falls under the category of normative legal research, using a statutory and conceptual approach. The data sources used include primary, secondary, and tertiary legal sources. Data collection was carried out through literature studies, followed by the processing and analysis of legal materials using a qualitative analysis method. The results of this study show that the actions of the Warkopi comedy group and its management constitute a violation of Copyright under Law No. 28 of 2014. Legal protection for the Warkop DKI film work consists of preventive legal protection by avoiding or preventing imitation of another's work, and repressive legal protection, which involves enforcement provisions as the final protection for creators or copyright holders by imposing proper punishment on those proven to infringe copyright. This proves that Warkopi's actions harmed Warkop DKI. The resolution of the copyright infringement dispute between Warkopi and Warkop DKI was conducted amicably, without litigation. Essentially, Warkopi has violated copyright law by deliberately committing illegal acts. Furthermore, Warkopi's responsibility for copying the Warkop DKI film without permission is to compensate for the harm caused to the Warkop DKI organization in accordance with Article 1365 of the Civil Code.